MODEL BANK WAKAF DI INDONESIA DALAM POTENSINYA UNTUK MENGEMBANGKAN WAKAF UANG DAN MENGATASI KEMISKINAN - Havita, Gusva; Sayekti, Kartika Arum; Wafiroh, Silvia Ranny (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
Waqf or endowment is one of the most unique Islamic economics instrument and has been developed rapidly all over the world. However, cash waqf as one of the most potential source of fund has not been empowered optimally in Indonesia. This proposal outlines the idea of building the most ideal and suitable waqf bank model that can be implemented in Indonesia to develop cash waqf and overcome poverty through the management of a variety of Islamic investments. The profits from this investment will be allocated mainly for developing education, health care, social services, and productive capital.